“Contadini e complici”: un dialogo con Ermanno Olmi - Colosio, Laura (Scienze del Territorio, 2014)
Responding to suggestions offered by Giorgio Ferraresi, in a dense dialogue/interview Ermanno Olmi, great artist and high witness of the past and present of rural civilisation, explains the sense that returning a new centrality to agriculture - and in particular to the ‘peasant way’ to its rediscovery - assumes within a general movement of redemption of nature from the subjugation and abandonment in which the industrialist and ‘developmentalist’ post-war choices seemed to have inexorably thrown it, in our country as elsewhere; showing how a mature and aware return to earth, with its matrix and prospects both territorial, but also cultural, social, economic and emotional, represents today the only possible escape from the general crisis of human settlement on Earth.